Given f, of, x, equals, minus, 3, x, squared, plus, 6, x, plus, 1f(x)=−3x 2 +6x+1, find f, of, 6f(6)
Question
Given
f(x) = -3x² + 6x + 1, find f(6)
Solution
To find the value of f(6), you need to substitute x = 6 into the function f(x) = -3x^2 + 6x + 1.
Step 1: Substitute x = 6 into the function f(6) = -3(6)^2 + 6(6) + 1
Step 2: Simplify the equation f(6) = -3(36) + 36 + 1 f(6) = -108 + 36 + 1
Step 3: Add the numbers f(6) = -71
So, f(6) = -71.
Similar Questions
Given f, of, x, equals, minus, 3, x, squared, plus, 6, x, plus, 1f(x)=−3x 2 +6x+1, find f, of, 6f(6)
Select the correct answer.If the factors of function f are (x − 6) and (x − 1), what are the zeros of function f?
Given f, left bracket, x, right bracket, equals, minus, 5, x, minus, 3f(x)=−5x−3, find f, left bracket, minus, 6, right bracketf(−6).
If f(2)=13𝑓(2)=13, which could be the equation for f(x)𝑓(𝑥)? f(x)=2x3+5𝑓(𝑥)=2𝑥3+5 f(x)=x+x2𝑓(𝑥)=𝑥+𝑥2 f(x)=3x2+1𝑓(𝑥)=3𝑥2+1 f(x)=x2+8𝑓(𝑥)=𝑥2+8
If f(x)=6x-4 , what is f(x) when x=8?
Upgrade your grade with Knowee
Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.